2020
DOI: 10.1111/acer.14339
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylethanol Levels in Postpartum Women and Their Newborns in Uruguay and Brazil

Abstract: Background: There is increasing interest in the development of newborn screening tests to identify children at risk of fetal alcohol spectrum disorder (FASD) in order to provide these children with early intervention. Phosphatidylethanol (PEth) has emerged as a potential universal newborn screening candidate.Methods: The aim of this report was to present the results of a study designed to compare PEth levels in 1,140 postpartum women and their newborn infants in Montevideo, Uruguay, and Sao Paulo, Brazil. Self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 48 publications
0
16
0
1
Order By: Relevance
“…All the included papers were original articles, of which there were seven prospective cohort/longitudinal studies [ 1 , 7 , 13 , 15 , 16 , 18 , 20 ], six cross-sectional studies [ 17 , 21 , 22 , 23 , 24 , 25 ], one retrospective study [ 26 ], and two observational-descriptive studies [ 27 , 28 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…All the included papers were original articles, of which there were seven prospective cohort/longitudinal studies [ 1 , 7 , 13 , 15 , 16 , 18 , 20 ], six cross-sectional studies [ 17 , 21 , 22 , 23 , 24 , 25 ], one retrospective study [ 26 ], and two observational-descriptive studies [ 27 , 28 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another study by the same authors revealed that 17% had a positive PEth sample after 3 to 4 weeks of abstinence when using a limit of quantification of 0.0031 µM (Kwak et al, 2014), that is, similar to our study. Studies with a larger number of participants have been carried out immediately after birth, where PEth has been measured in dried blood spots or umbilical cord blood (Bakhireva et al, 2014; Bakhireva et al, 2017; Baldwin et al, 2020; Bracero et al, 2017; Maxwell et al, 2019). These studies have shown a significantly higher proportion of alcohol‐exposed pregnancies than in our study.…”
Section: Discussionmentioning
confidence: 99%
“…PEth analysis has been applied to study prenatal alcohol exposure and emerged as a potential universal newborn screening candidate (Bakhireva et al, 2014; Baldwin et al, 2020). Besides the DBS of newborns, also elevated PEth concentrations in maternal material are indicative of exposure to maternal alcohol consumption during the last 3–4 weeks of pregnancy (Baldwin et al, 2020).…”
Section: Applicationsmentioning
confidence: 99%
“…PEth analysis has been applied to study prenatal alcohol exposure and emerged as a potential universal newborn screening candidate (Bakhireva et al, 2014; Baldwin et al, 2020). Besides the DBS of newborns, also elevated PEth concentrations in maternal material are indicative of exposure to maternal alcohol consumption during the last 3–4 weeks of pregnancy (Baldwin et al, 2020). PEth might be especially useful as a cost‐effective screening for children at risk of fetal alcohol spectrum disorder in high‐risk populations where prenatal alcohol use is common (Bakhireva et al, 2013; Baldwin et al, 2020).…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation